If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + y)(x + y)(x + y) = 0 Multiply (x + y) * (x + y) (x(x + y) + y(x + y))(x + y) = 0 ((x * x + y * x) + y(x + y))(x + y) = 0 Reorder the terms: ((xy + x2) + y(x + y))(x + y) = 0 ((xy + x2) + y(x + y))(x + y) = 0 (xy + x2 + (x * y + y * y))(x + y) = 0 (xy + x2 + (xy + y2))(x + y) = 0 Reorder the terms: (xy + xy + x2 + y2)(x + y) = 0 Combine like terms: xy + xy = 2xy (2xy + x2 + y2)(x + y) = 0 Multiply (2xy + x2 + y2) * (x + y) (2xy * (x + y) + x2(x + y) + y2(x + y)) = 0 ((x * 2xy + y * 2xy) + x2(x + y) + y2(x + y)) = 0 Reorder the terms: ((2xy2 + 2x2y) + x2(x + y) + y2(x + y)) = 0 ((2xy2 + 2x2y) + x2(x + y) + y2(x + y)) = 0 (2xy2 + 2x2y + (x * x2 + y * x2) + y2(x + y)) = 0 Reorder the terms: (2xy2 + 2x2y + (x2y + x3) + y2(x + y)) = 0 (2xy2 + 2x2y + (x2y + x3) + y2(x + y)) = 0 (2xy2 + 2x2y + x2y + x3 + (x * y2 + y * y2)) = 0 (2xy2 + 2x2y + x2y + x3 + (xy2 + y3)) = 0 Reorder the terms: (2xy2 + xy2 + 2x2y + x2y + x3 + y3) = 0 Combine like terms: 2xy2 + xy2 = 3xy2 (3xy2 + 2x2y + x2y + x3 + y3) = 0 Combine like terms: 2x2y + x2y = 3x2y (3xy2 + 3x2y + x3 + y3) = 0 Solving 3xy2 + 3x2y + x3 + y3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| -4(1-8p)=-100 | | (x+y)(x+y)(x+y)=1 | | 0=-16t+44t+5 | | 83=6(n+3)+7n | | (3x-7)(4x+7)=0 | | y=[x]2+8x | | 2x+16x+5=0 | | x-.17=504.23 | | 2x^2-y^2=41 | | r(-50)=0 | | x-.17x=504.23 | | x-3(10-3x)=100 | | 1=1-x-4x | | 16=1/2h^2 | | x-.24x=465.12 | | 0.06(x^2)+0.15y(30-x)=0.12(8x) | | 6r+5-3r=-4 | | (m+7)(m-8)= | | x-.24=465.12 | | 8m+19=-10 | | Log(9-4c)=2.5 | | -7p+2(-3p+2)=4(p+1) | | P=8n+4 | | 0.5/2a/3 | | 18=1-8p+1 | | 4+3n-8n=-3n-8+n+6 | | 8+6(6+6m)=116 | | 3h-1=5 | | 18-3n=4n+11 | | 13+8m=7m+14 | | w+15=2 | | 1-7y=2y-14 |